Analog Rice from Pedada Fruit Composite Flour as Functional Food with Low Glycemic Index - Diella Trisna Ayuningtyas; Avina Rachma Saraswati; Jariyah Jariyah (The University of Lampung, 2025)
This study aims to determine the effect of composite flour proportion pedada fruit, white corn, and soybean flours as well as the addition of GMS on the physicochemical and organoleptic properties of analog rice as functional food that is safe for people with Diabetes Mellitus. This study was arranged in a factorial completely randomized design consisting of two factors with nine treatment combinations and three replications. Factor 1 was the proportion of flour materials pedada fruit-white corn-soybean (5%-75%-20%, 10%-70%-20%, 15%-65%-20%). Factor 2 was GMS addition (1%, 2%, 3%). The data was analyzed using ANOVA at the 5% level and continued with the Duncan Multiple Range Test (DMRT). The results showed that the best treatment was the A1B1 formulation consisting of 5% pedada fruit flour, 75% white corn flour, 20% soy flour and the addition of 1% GMS produced analog rice with organoleptic characteristics of color getting a value of 3.48 (like), aroma 2.92 (neutral), texture 2.76 (neutral), and taste 3 (neutral), antioxidant content of 47.73%, in vitro glycemic index of 42. The results of the RVA analysis showed that formulation A1B1 had a pasting temperature of 94.8°C, peak viscosity 184 cP, hold viscosity 183 cP, final viscosity 332 cP, breakdown 1 cP, setback 149 cP.